Upaya Mendorong Perkembangan Minat Belajar Anak Usia Dini Dengan Menggunakan Media APE (Peralatan Bermain Edukatif) - Ismawati Azzola (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
Early childhood is a child in the golden period of growth. By providing stimulus for their growth and development by stimulating them using APE. Educational Play Tools (APE) are expected to make learning interesting. and interesting. fun, so that children feel at home, don't get bored and focus on learning. Even though it is known that educational teaching aids (APE) really support the implementation of effective learning, schools require more optimal use of educational teaching aids (APE) in the learning process. The aim of the activity is to increase children's interest in learning, the department carries out actions with the help of educational toys (HPE) prepared by teachers in accordance with the basic needs of the subjects taught to children. and can be obtained easily using existing purchased item materials. used or other forms of creativity that can be designed, created, used and exploited, especially teachers who have the necessary skills to equip themselves through socialization, training and seminars to learn more and need new things in the form of knowledge and skills.